2021
DOI: 10.1155/2021/7308816
|View full text |Cite
|
Sign up to set email alerts
|

Suspender Replacement Method for Long‐Span Concrete‐Filled Steel Tubular Arch Bridges and Cable Force Measurement Based on Frequency Method

Abstract: The suspenders on the sides of an arch bridge are highly vulnerable to damage caused by traffic load and environmental corrosion. To accurately estimate the cable force of suspenders, herein, we analyse the influencing factors through a suspender tension test based on the principle of suspender vibration. The frequency of each suspender of the bridge is evaluated using the frequency method. By combining the cable force data measured directly and the measured suspender frequency, the formulas for calculating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…e layout of the bridge lanes is shown in Figure 3, and the management and maintenance unit in this area has established a dynamic weighing system to record the number of vehicles in the driving lane, vehicle speed, vehicle mass, axle load, axle number, wheelbase, and other parameters. ese basic data can provide an important basis for the fatigue assessment of the bridge and can be used to estimate the service life of the bridge suspenders [22].…”
Section: Vehicle Statistics Of the Dynamic Load-mentioning
confidence: 99%
“…e layout of the bridge lanes is shown in Figure 3, and the management and maintenance unit in this area has established a dynamic weighing system to record the number of vehicles in the driving lane, vehicle speed, vehicle mass, axle load, axle number, wheelbase, and other parameters. ese basic data can provide an important basis for the fatigue assessment of the bridge and can be used to estimate the service life of the bridge suspenders [22].…”
Section: Vehicle Statistics Of the Dynamic Load-mentioning
confidence: 99%
“…In the management of the complete service life cycle of steel tube concrete arch bridges, the performance of suspenders and the steel wires inside them is a crucial consideration. Previous field surveys have indicated that under the influence of complex stresses, there is a probability of damage to the outer layer sheath of the suspenders, leading to the infiltration of water molecules and causing electrochemical corrosion inside the suspenders [1]. During the service life of a bridge, highly humid areas may develop within the suspender, leading to corrosion of the steel wires.…”
Section: Introductionmentioning
confidence: 99%
“…Although the suspender replacement is technically feasible, the repair is expensive [2,3]. The bridge that provided the sample for this experiment also faced the problem of replacing the suspender [4]. Effective corrosion control measures can only delay the corrosion of the suspender [5].…”
Section: Introductionmentioning
confidence: 99%